Stress Distribution in Composites with Co-Phase Periodically Cured Two Neighboring Hollow Fibers - Kosker, Resat; Gulten, Ismail (TECH SCIENCE PRESS, 2021)
In this paper, stress distribution is examined in the case where infinite length co-phase periodically curved two neighboring hollow fibers are contained by an infinite elastic body. The midline of the fibers is assumed to be in the same plane. Using the three-dimensional geometric linear exact equations of the elasticity theory, research is carried out by use of the piecewise homogeneous body model. Moreover, the body is assumed to be loaded at infinity by uniformly distributed normal forces along the hollow fibers. On the inter-medium between the hollow fibers and matrix surfaces, complete cohesion conditions are satisfied. The boundary form perturbation method is used to solve the boundary value problem. In this investigation, numerical results are obtained by considering the zeroth and first approximations to calculate the self-equilibrium shear stresses and normal stress at the contact surfaces between the hollow fibers and matrix. Numerous numerical results have been obtained and interpreted about the effects of the interactions between the hollow fibers on this distribution.
Keywords: Hollow fibers; stress distribution; fibrous composite; periodic curvature; INFINITE ELASTIC BODY; CURVED FIBERS; ROW; Computer Science; Materials Science